2014
DOI: 10.1590/0101-60830000000033
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous use of alcohol among undergraduate students at a public university

Abstract: Background: The potentially harmful consequences of alcohol use among undergraduates have become a growing concern in recent years. Objectives: This study aimed to determine the prevalence of hazardous use of alcohol in this population and to identify demographic and psychosocial factors associated with this pattern of consumption. Methods: This was a cross-sectional study using an anonymous and self-completed questionnaire in the classroom. The questionnaire was administered to 1,290 enrolled male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…However, university parties usually last longer than 2 hr, in which case the intake of five doses would not reach an alcohol concentration of 0.08 g/L for most young people in a period exceeding 2 hr (Courtney & Polich, 2009). As the period of consumption was circumscribed, it would be expected that the binge consumption rates found in this study would be lower than those of other Brazilian studies, however similar rates were observed (Andrade et al, 2010;Santos et al, 2014). The data presented in our investigation indicate that 25.3% of college students had taken part in binge consumption in the past month, whereas in the United States this frequency was of 39% (SAMHSA, 2014).…”
Section: Alcohol Consumption and Binge Drinkingsupporting
confidence: 53%
“…However, university parties usually last longer than 2 hr, in which case the intake of five doses would not reach an alcohol concentration of 0.08 g/L for most young people in a period exceeding 2 hr (Courtney & Polich, 2009). As the period of consumption was circumscribed, it would be expected that the binge consumption rates found in this study would be lower than those of other Brazilian studies, however similar rates were observed (Andrade et al, 2010;Santos et al, 2014). The data presented in our investigation indicate that 25.3% of college students had taken part in binge consumption in the past month, whereas in the United States this frequency was of 39% (SAMHSA, 2014).…”
Section: Alcohol Consumption and Binge Drinkingsupporting
confidence: 53%
“…14 The prevalence of hazardous use of alcohol among undergraduate students at a public university in Brazil was 24%. 15 Patterns of alcohol use on a South African university campus showed 8.5% of the undergraduate students have harmful alcohol consumption. 16 The relationship between alcohol consumption and perceived social support (PSS) is complex; perhaps even more so among those with AUD.…”
Section: Introductionmentioning
confidence: 99%